2019
DOI: 10.1002/mma.5548
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of fractional‐order chaotic systems with disturbances via novel fractional‐integer integral sliding mode control and application to neuron models

Abstract: In this paper, a novel fractional‐integer integral type sliding mode technique for control and generalized function projective synchronization of different fractional‐order chaotic systems with different dimensions in the presence of disturbances is presented. When the upper bounds of the disturbances are known, a sliding mode control rule is proposed to insure the existence of the sliding motion in finite time. Furthermore, an adaptive sliding mode control is designed when the upper bounds of the disturbances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Similar to the Hopfield neural network, the Hindmarsh-Rose neuron is quite useful, for example: using the Hindmarsh-Rose neuron model, the authors in [16] showed that in the parameter region close to the bifurcation value, where the only attractor of the system is the limit cycle of tonic spiking type, the noise can transform the spiking oscillatory regime to the bursting one. The fractional-order version of the Hindmarsh-Rose neuron was used in [17], for the synchronization of fractional-order chaotic systems. In [18], based on two-dimensional Hindmarsh-Rose neuron and non-ideal threshold memristor, a five-dimensional neuron model of two adjacent neurons coupled by memristive electromagnetic induction, was introduced.…”
mentioning
confidence: 99%
“…Similar to the Hopfield neural network, the Hindmarsh-Rose neuron is quite useful, for example: using the Hindmarsh-Rose neuron model, the authors in [16] showed that in the parameter region close to the bifurcation value, where the only attractor of the system is the limit cycle of tonic spiking type, the noise can transform the spiking oscillatory regime to the bursting one. The fractional-order version of the Hindmarsh-Rose neuron was used in [17], for the synchronization of fractional-order chaotic systems. In [18], based on two-dimensional Hindmarsh-Rose neuron and non-ideal threshold memristor, a five-dimensional neuron model of two adjacent neurons coupled by memristive electromagnetic induction, was introduced.…”
mentioning
confidence: 99%
“…Chaotic systems are applicable in a wide range of research classifications such as jerk systems [1,2], robotics [3,4], neuron models [5,6], oscillators [7,8], circuits [9][10][11], biological systems [12,13], chemical systems [14,15], and memristors [16,17]. In view of their attractive triangular structure, considerable numbers of papers have been published on the chaos jerk models [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…According to the biological characteristics of neurons, the types of synchronization for neuron systems include GPS [26], [27], complete synchronization (CS) [25], [28], lag synchronization (LS) [29], anti-phase synchronization (APS) [30], and generalized function projective synchronization (GFPS) [31]. For the nonlinear and chaotic characteristics of neuronal models, various control methods have been applied in the synchronization of neurons, such as feedback control, neural network control, adaptive control, and slide mode control, by using the linear matrix inequality and Lyapunov theory [25], [28], [29], [32]- [34].…”
Section: Introductionmentioning
confidence: 99%
“…For HR neuron systems subject to asymmetrical time delays, Fan et al discussed how the time delays and coupling strengths affected the lag synchronization and transmission of firing modes between neurons [29]. Vajiheh et al introduced a sliding mode technique for GPS in fractional-order systems and implemented it in classical HR neuronal models [31].…”
Section: Introductionmentioning
confidence: 99%